2020
DOI: 10.1152/ajplung.00302.2019
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory mechanics during initial lung aeration at birth in the preterm lamb

Abstract: Despite recent insights into the dynamic processes during lung aeration at birth, several aspects remain poorly understood. We aimed to characterize changes in lung mechanics during the first inflation at birth and their relationship to changes in lung volume. Intubated preterm lambs (gestational age, 124–127 days; n = 17) were studied at birth. Lung volume changes were measured by electrical impedance tomography (VL EIT). Respiratory system resistance (R5) and oscillatory compliance (Cx5) were monitored with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…At birth the lung is fluid filled, and airways (and tissue) have a high resistance. (34) The left main bronchus exits the carina acutely, and is encumbered by the heart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At birth the lung is fluid filled, and airways (and tissue) have a high resistance. (34) The left main bronchus exits the carina acutely, and is encumbered by the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Crying created different flow characteristics than tidal breathing, quickly inflating the lung with faster Ti and PIF. This is advantageous within the highly resistive fluid-filled lung at birth, (34) but once aerated provides little mechanical or gas exchange benefit. We postulate that crying has a de novo physiological purpose, and not simply due to the noxious stress response of birth.…”
Section: Discussionmentioning
confidence: 99%
“…X 5 changes during SI at birth in preterm lambs, although of variable magnitude, present the same pattern for all lambs: X 5 increases like an exponential function during SI and after-SI X 5 improved compared with before-SI X 5 . 16 In infants, we found that the increase of X 5…”
Section: Discussionmentioning
confidence: 84%
“…7 The lung is in a state of flux in early ex-utero life; the alveoli maybe air-filled but fetal lung fluid remains in the interstitium, and fluid can influx back into alveoli if the intrathoracic pressure gradient falls, compromising FRC. 4,8,25 It has been proposed that 'expiratory braking' is essential during this period, 1,[5][6][7]15,16 and flow patterns measured at the airway opening support this, but have not been correlated to temporal FRC change. 14…”
Section: Discussionmentioning
confidence: 99%
“…At birth the lung is fluid filled, and airways (and tissue) have a high resistance. (34) The left main bronchus exits the carina acutely, and is encumbered by the heart. This may create preferential flow states towards the right lung, especially during the higher inspiratory flows of crying.…”
Section: Discussionmentioning
confidence: 99%